Paediatric traumatic cardiac arrest: data from the Joint Theatre Trauma Registry. Issue 4 (26th June 2015) - Hillman, Christopher M; Rickard, A; Rawlins, M; Smith, JE
Abstract : Background: Traumatic cardiac arrest (TCA) in children is associated with a low probability of survival and poor neurological outcome in survivors. Since 2003, over 600 seriously injured local national children have been treated at deployed UK military medical treatment facilities during the Iraq and Afghanistan conflicts. A number of these were in cardiac arrest after sustaining traumatic injuries. This study defined outcomes from paediatric TCA in this cohort. Methods: A retrospective database review was undertaken using the UK Joint Theatre Trauma Registry. This includes UK military, coalition military, civilians and local security forces personnel who prompted trauma team activation. All children in this series were local nationals. Patients aged less than 18 years who presented between January 2003 and April 2014, and who underwent cardiopulmonary resuscitation, were included. Results: 27 children with TCA were included. Four children survived to discharge from the medical treatment facility (14.8%), though limited data are available regarding the long-term neurological outcome in these patients. Conclusions: This study demonstrates that the outcomes for paediatric TCA in our military field hospitals were similar to other paediatric civilian and adult military studies, despite patients being injured by severe blast injuries. Further work is needed to define the optimal management of paediatric TCA.